Implementation of Youtube Video Tutorials in Improving Understanding of Islamic Cultural History Material in Class X MAN 1 Sukabumi City - Ridhwanullah Husain Al-Fawaz; Sofwan Sofwan; Rosita Rosita; Cecep Hilman (Journal of Pedagogi, 2025)
YouTube video tutorials have become an effective learning medium to enhance students' understanding of educational materials, including Islamic Cultural History. This study aims to examine the impact of YouTube video tutorials on students' comprehension. Using a qualitative approach, data were collected through interviews, direct observations, and document studies at a secondary school in Indonesia. The findings indicate that YouTube video tutorials significantly improve students' interest in learning, provide a deeper understanding through visual and auditory elements, and increase engagement in the learning process. The visual representation of historical events makes abstract concepts more tangible, allowing students to grasp complex ideas more easily. Additionally, the flexibility of video tutorials enables students to revisit materials at their own pace, reinforcing their understanding. Teachers also find these videos useful as supplementary teaching tools, helping them present historical narratives in a more engaging and accessible manner. Furthermore, students show greater enthusiasm in discussions and assignments after watching the tutorials. In conclusion, YouTube video tutorials serve as an innovative and effective medium for enhancing students' understanding of Islamic Cultural History, offering an interactive and accessible way to present historical concepts while fostering deeper engagement in the learning process